(untitled) (Ozone Therapy Global Journal, 2021)
Introduction: Currently there are no protocol treatments for persistent pain in Painful Blind Eye. Different strategies have been used for years such as topical therapy, NSAIDs, retro-bulbar injections and stellate ganglion block. These are not always effective or uncomplicated. Enucleation or eye evisceration has been the definitive pain treatment in patients with Painful Blind Eye. But this surgical option represents an emotional shock for most patients. On the other hand, many of these eyes may be aesthetically acceptable or may not be candidates for surgery. Therefore, it is urgent to have new effective therapeutic tools for this entity since pain treatment represents a great challenge for most ophthalmologists worldwide. Case Report: 60-year-old female patient with painful blind eye diagnosis, for the last 3 months, reporting moderate to severe intensity, refractory to different treatments and compromising her sleep and daily activities. She was treated with 4 ozone-therapy sessions (15 µg / mL subconjunctival and / or subcutaneously) showing pain resolution and symptoms improvement. Conclusions: The Painful Blind Eye can be a very debilitating condition. Ozone-therapy could be considered as a treatment option when conventional medical management has failed. It is an easy application tool for the ophthalmologist, effective and with no side effects, which opens up a new field of research in the area.